Sistema penitenciário federal: o quarto regime de cumprimento de pena no estado de coisas inconstitucional - Lemos, Emilly Duarte (Universidade Federal Rural do Semi-Árido, 2018)
Analyzing the structure of the Brazilian Federal Penitentiary System (FPS), based on its characteristics in relation to criminal law, criminal procedure and constitutional warrants, this study aims to make observations from the point of view of the Unconstitutional State of Things (UST) extant in the Brazilian prison system, about the possibility of classifying it as a fourth and new regime of compliance with the criminal sanction. This paper was developed in three stages, and bibliographical research was used in all of them to carry out structuring on the theme. In the first part, it was tried to raise a brief panorama about the theories of sentence and the regimes of fulfillment of the penal sanction. In its second and third parts, the objective of this study was to outline the particular characteristics that guide the Brazilian Federal Penitentiary System and to analyze whether, due to the UST existing in the Brazilian penitentiary system, it became a new regime of compliance with the criminal sentence. Finally, it is concluded that the peculiarities inherent in federal maximum security establishments are the reasons for it to present itself as the institution of a fourth system of compliance with the penal sanction, mainly due to the State of Things Unconstitutional in the prison system Brazilian.
Artigo Acadêmico
Keywords: Sistema penitenciário federal; Estado de coisas inconstitucional; Regimes de cumprimento de pena; Federal penitentiary system; Unconstitutional state of things; Penalties enforcement; Criminal execution; CIENCIAS SOCIAIS APLICADAS::DIREITO